Parâmetros clínicos, periodontais, nutricionais e imaginológicos em pacientes em uso de inibidores de aromatase - Alessandra Figueiredo de Souza (2022)
Osteoporosis is a multifactorial systemic disease characterized by reduced bone mass. Osteoporosis can be primary or secondary to the use of drugs such as aromatase inhibitors. These drugs interfere with the conversion of androgens to estrogens, reducing their production and are indicated for the treatment of estrogen-dependent breast cancer. The diagnosis of osteoporosis is based on densitometric criteria of the World Health Organization with reference to the T-score classification, performed by the technique of dual energy x-ray absorptiometry (DXA). Because it is a systemic disease, osteoporosis also affects the jaw bones. However, the occurrence and extent of loss of alveolar bone structure in osteoporosis, as well as the risk of these patients for periodontal disease and tooth loss, are not clearly defined. This study aimed to identify clinical, periodontal, nutritional and biochemical determinants involved with bone loss in patients using aromatase inhibitors. Bone loss was assessed by dual X-ray absorptiometry (DXA). Data on nutritional, anthropometric, oral and periodontal status and oral health-related quality of life (OHRQoL) were collected. Cytokines and adipokines were quantified in saliva and serum. A cross-sectional case-control type study, with a comparison group, was conducted at the bone densitometry service of Hospital Mater Dei from 2018 to 2021. The sample consisted of 72 women divided into two groups: using aromatase inhibitors (AIs) (n=40) and patients not using aromatase inhibitors (control) (n=32). Of the total sample, 39 patients (57.4%) were diagnosed with bone loss. The results showed that elderly women using aromatase inhibitors (p=0.009) and smokers (p=0.034) had greater bone loss. There was no significant difference between the groups considering the analyzed comorbidities. Anthropometric analysis showed that individuals using aromatase inhibitors with bone loss had lower weight (p=0.028). The regression model revealed that the only variable that explains bone loss is the use of antiresorptive drugs, with bone loss significantly reduced in individuals who used this medication (p=0.022). Although the frequency of periodontitis was similar comparing all groups, higher values of IL-6 (p=0.004); IL-1β (p=0.002) and IL-33 (p=0.006) in saliva were related to worse periodontal status. Subjects who used aromatase inhibitors were 1.18 times more likely to report a better oral health-related quality of life (OHRQoL) than controls. Conclusion: While advanced age, smoking and lower weight are factors associated with bone loss, the use of antiresorptives was a protective factor in individuals using aromatase inhibitors.